Conidial emulsion formulation and thermal storability of Metarhizium anisopliae against red palm weevil, Rhynchophorus ferrugineus olivier (Coleoptera: Dryophthoridae) - Cheong, Jia Lei; Abdul Halim, Najihah; Asib, Norhayu; Zakaria, Azlina; Azmi, Wahizatul Afzan (MDPI, 2022)
Industrial crops including coconut palm and other palm species are seriously infested by red palm weevil (RPW), resulting in significant economic damage globally. Therefore, this study aimed to develop a mycoinsecticide utilizing conidia of Metarhizium anisopliae to control RPW and sought to investigate a new emulsion formulation for the influences of storage temperature and heat stress on conidia germination in an oil-in-glycerol emulsion system. The mycoinsecticide is an emulsion formulation which comprises an oil carrier, non-ionic surfactants, water, and glycerol, which was optimized by premixing the oil and non-ionic surfactant in different weight ratios (1:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4: 6, 3: 7, 2:8, 1:9, and 0:1). From three selected oil-in-glycerol formulations, F25 was more stable in storage and had a smaller particle size (between 154.3 and 236.4 nm in diameter) and stable zeta potential (above + 30 mV) with low surface tension (29.83 ± 0.24 mN/m to 30.72 ± 0.11 mN/m at room temperature. Extended conidial viability was observed at 4 °C overall; the emulsion formulation maintained 12–15% conidial viability until the eighth week at room temperature. Heat of over 30 °C showed an inhibitory effect on conidial germination. This study revealed that the oil-in-glycerol formulation was stable and able to prolong conidial shelf life as compared to non-formulated conidia.